Pengaruh Kepemilikan Keluarga terhadap Kinerja Perusahaan Studi Empiris Perusahaan di Bursa Efek Indonesia Tahun 2011 - Isma Arief Dharmawan; Erric Wijaya (Jurnal Keuangan dan Perbankan, 2014)
This research on the influence of family’s ownership structure towards company’s performance. On this research, company’s performance uses two proxies, which are Return on Assets for measuring company’s operational performance and Tobins Q for measuring company’s market performance. Family’s ownership is presented by dummy variable. The samples for this research are amounting 364 non financial companies which are listed on Indonesia Stock Exchange on 2011. Those samples were designated by using purposive sampling method and were preceded by using multiple regression. Based on this research, it has shown that company with family’s ownership structure had not given any significant influence towards company’s operational performance (ROA). However, company with family’s ownership influences the company’s market performance negatively (Tobins Q).